Letter from Aaron Clement on behalf of the Philadelphia Society for Promoting Agriculture to James Curtis Booth - Clement, Aaron (1852)
Letter from Aaron Clement, recording secretary of the Philadelphia Society for Promoting Agriculture, informing James Curtis Booth (1810-1888) that he has been unanimously elected a member of the society.
Keywords: Booth, James Curtis, 1810-1888; Private clubs; Philadelphia Society for Promoting Agriculture; Societies